Multiaxial fatigue strength assessment of electroslag remelted 50CrMo4 steel crankshafts. (July 2017) - Leitner, M.; Tuncali, Z.; Steiner, R.; Grün, F.
Highlights: Effect of electroslag remelting (ESR) process on uniaxial fatigue strength. Multiaxial fatigue strength characterization of material in ESR condition. Application of equivalent stress criteria utilizing the cutting plane approach. Abstract: This work investigates the fatigue strength of multiaxially-loaded gas engine crankshafts incorporating electroslag remelted 50CrMo4 steel. Uniaxial fatigue tests with small-scale round specimens before and after performing the ESR process are conducted. The results reveal that the high-cycle fatigue strength at the run-out region significantly decreases by 21% if no ESR-treatment is performed. Multiaxial fatigue tests under proportional normal and shear stress loading demonstrate that the elliptical model by Gough and Pollard leads to a minor underestimation of 5% compared to the test results. An application of several state-of-the-art equivalent stress hypotheses utilizing the critical plane approach is presented and the estimated results are compared to the experiments in terms of high-cycle fatigue resistance and crack initiation angle.